1996
DOI: 10.1200/jco.1996.14.9.2527
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitomycin in combination with fluorouracil and radiotherapy, and of salvage chemoradiation in the definitive nonsurgical treatment of epidermoid carcinoma of the anal canal: results of a phase III randomized intergroup study.

Abstract: Despite greater toxicity, the use of MMC in a definitive CR regimen for anal cancer is justified, particularly in patients with large primary tumors. Salvage CR should be attempted in patients with residual disease following definitive CR before resorting to radical surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
633
6
38

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 998 publications
(709 citation statements)
references
References 29 publications
32
633
6
38
Order By: Relevance
“…A boost of 15 Gy (for complete responders), or 20 Gy (for partial responders), was given at 6 weeks using photons, electrons or an iridium 192 implant. This contrasts with the RTOG trial, which used a complex shrinking field technique to 45 Gy in 1.8 Gy fractions, with field sizes reduced at 30.6 and 36 Gy (Flam et al, 1996). If the primary tumour was still palpable after 45 Gy, a further 5.4 Gy was given in three fractions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A boost of 15 Gy (for complete responders), or 20 Gy (for partial responders), was given at 6 weeks using photons, electrons or an iridium 192 implant. This contrasts with the RTOG trial, which used a complex shrinking field technique to 45 Gy in 1.8 Gy fractions, with field sizes reduced at 30.6 and 36 Gy (Flam et al, 1996). If the primary tumour was still palpable after 45 Gy, a further 5.4 Gy was given in three fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a Radiation Therapy and Oncology Group (RTOG) and Eastern Cooperative Oncology Group (ECOG) trial showed that MMC combined with 5-FU was superior to 5-FU alone when combined with radiation for colostomy-free survival (Flam et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the UKCCCR anal trial this combination proved the effective one. Interestingly, one study compared this combination with one dropping the mitomycin for anal carcinoma (Flam et al, 1996) and a difference was seen in local control. Mitomycin may be important in its radiosensitizing effect, perhaps because of its effect on hypoxic cells.…”
Section: Which Chemotherapeutic Agents?mentioning
confidence: 99%
“…The use of chemotherapy in combination with radiotherapy was first evaluated in the early 1970s by a group at Wayne State University. Working on the observation that the use of fluoropyrimidine-based chemotherapy potentiates radiation, Nigro and colleagues used preoperative 5-fluorouracil (5-FU) (1000 mg/m 2 continuously on days 1-4 and 29-32) and mitomycin (10-15 mg/m 2 on day 1) in combination with moderate-dose (30 Gy) external beam radiation therapy (EBRT) 4. The first three patients treated with this regimen had no evidence of residual disease at the time of surgery, raising the question of whether combined chemoradiation therapy obviated the need for APR.…”
mentioning
confidence: 99%